2018
DOI: 10.15406/mojddt.2018.02.00066
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening of Leucaena leucocephala leaf essential oil and its antibacterial potentials

Abstract: Objective: The study aimed to identify the phytochemical composition of Leucaena leococephala leaf and evaluate the antimicrobial potential of the essential oil from the leaf. Material and Methods: The sample was subjected to Clevenger apparatus to extract the oil. The essential oil was characterized by chromatography method (GC-MS). The GC-MS was performed on Perkin Elmer gas chromatography model Clarus 680 equipped with HP-5 fused capillary column (5%) phenylmethyl polysiloxane stationary phase with 30m leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…As expected, 2-methylisoborneol and geosmin were detected. Likewise, different compounds with antimicrobial activity were detected, such as furanones, dimethyl disulfide, 2,6,6-trimethyl-1-Cyclohexene-1-acetaldehyde, and muurola derivatives [53,57,58]. It is worth highlighting the production of caryophyllenyl alcohol, identified in several samples in both media and associated with several applications in cosmetics and derivatives in the drug industry (hypolipidemic, anti-inflammatory properties [59][60][61][62].…”
Section: Cocultured E Weberi-streptomyces Sp Cs131mentioning
confidence: 98%
See 1 more Smart Citation
“…As expected, 2-methylisoborneol and geosmin were detected. Likewise, different compounds with antimicrobial activity were detected, such as furanones, dimethyl disulfide, 2,6,6-trimethyl-1-Cyclohexene-1-acetaldehyde, and muurola derivatives [53,57,58]. It is worth highlighting the production of caryophyllenyl alcohol, identified in several samples in both media and associated with several applications in cosmetics and derivatives in the drug industry (hypolipidemic, anti-inflammatory properties [59][60][61][62].…”
Section: Cocultured E Weberi-streptomyces Sp Cs131mentioning
confidence: 98%
“…2,6,6-Trimethyl (beta-homocyclocitral)1-cyclohexene-1-acetaldehyde [51] and 1,3,3trimethyl-tricyclo [2.2.1.0(2,6)] heptane (cyclofenche) [52] are compounds with antifungal activities present in essential oils. Similarly, 4,8-dimethylnona-1,3,7-triene is also described as a monoterpene part of plant essential oils with antifungal activities [53]. 3-Octanone has been described as an antifungal cetone [54].…”
mentioning
confidence: 99%
“…Propolis extract has been shown to exhibit antimicrobial activity against ciprofloxacinsensitive and ciprofloxacin-resistant N. gonorrhoeae strains, in a study by Vică et al; depending on the harvesting region, the extracts presented with various inhibition zone diameters and MICs [130] (Appendix B, Table A5). Umaru et al studied the effect of Molineria capitulate fruit EO on various pathogens and showed that both M. capitulate EO and its major component, myrcene, displayed antimicrobial activity against N. gonorrhoeae strains [131]. Soliman et al investigated the antimicrobial properties of two guava (Psidium spp.)…”
Section: Neisseria Gonorrhoeae Cephalosporin-resistant Fluoroquinolon...mentioning
confidence: 99%
“…Sygzinium polyanthum with its synonym Eugenia Polyantha contain active compounds as antioxidants [121]. Compounds in S. polyanthum acting as antioxidants are pyrogallol, gallic acid, myrecitin, farnesol, phytol, and tocopherol [122,123]. The antioxidant compounds in S. polyanthum are shown in Figure 5.…”
Section: Antioxidant Activity Of S Polyanthum Leavesmentioning
confidence: 99%